The puzzling success of populist parties in promoting women's political representation. (July 2017) - Kostadinova, Tatiana; Mikulska, Anna
Previous research dismisses the possibility that populist, male-dominated parties could positively affect gender equality. Yet, evidence from Eastern Europe points at the opposite: Center-rightist formations, led by notable men, have effectively nominated women to office. What can explain such a puzzling phenomenon? This study argues that i) the centralized structure and practices in these populist parties make it possible to avoid the reluctance of gatekeepers to let female candidates run; and that ii) regardless of ideological or cultural predispositions, supporters loyally approve the nomination decisions made by their charismatic leader. We analyze data on three populist parties in Bulgaria and Poland. Our findings confirm that these formations elected more women than the leftist parties because of strategies to nominate female candidates higher on the list. Voters were also more likely to favor female candidates in the open-list system in Poland.